Ethics and social acceptability of a proposed clinical trial using maternal gene therapy to treat severe early‐onset fetal growth restriction. (9th March 2016) - Sheppard, M.; Spencer, R. N.; Ashcroft, R.; David, A. L.; ,
ABSTRACT: Objective: To evaluate the ethical and social acceptability of a proposed clinical trial using maternal uterine artery vascular endothelial growth factor (VEGF) gene therapy to treat severe early‐onset fetal growth restriction (FGR) in pregnant women. Methods: We conducted a literature review on the ethics and legality of experimental treatments in pregnant women, in particular advanced therapeutics. Issues that were identified from the literature helped develop interview guides for semistructured, qualitative interviews, carried out in four European countries, with 34 key stakeholders (disability groups, professional bodies and patient support groups) and 24 women/couples who had experienced a pregnancy affected by severe early‐onset FGR. Results: The literature review identified two main questions: 'is it ethical to give a pregnant woman a potentially risky treatment from which she does not benefit directly?' and 'is it ethical to treat a condition of the unborn child, who may then be born with a serious disability when, without treatment, they would have died?'. The review concluded that there were no ethical or legal objections to the intervention, or to a trial of this intervention. Overall, respondents viewed the proposed trial in positive terms. Women were generally interested in participating in clinical trials that conferred a potential benefit to their unborn child. The risk of disability of the premature child was a concern, but not considered a major stumbling block for maternal VEGF gene therapy. Conclusions: This study did not identify any fundamental or insurmountable objections to a trial of maternal gene therapy for severe early‐onset FGR. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.